Effectiveness of Informational Support on Anxiety among Family Carers of Patients Undergone Open Heart Surgery - Hamid Haghani; Naiemeh Seyedfatemi; Zahra Heidari; Masoomeh Imanipour (Tehran University of Medical Sciences, 2012)
Background & Objective: Hospitalization of patients in the intensive care unit of open heart surgery (ICUOH) is often stressful for patients' family carers. This study aimed to investigate the effectiveness of the informational support on anxiety among families of patients undergone open heart surgery. Methods & Materials: In this double-group randomized clinical trial, 64 family carers of patients undergone open heart surgery were selected using convenience sampling method and were randomly allocated into two intervention or control groups. The informational support consistedof  holding the ICU orientation tours and educational sessions, and providing educational pamphlets and booklets. The members of the control group received routin information. The anxiety of the family carers was measured using the trait Spielberger anxiety questionnaire before surgery and in the day of discharge from the ICU. Independent and paired t-tests were used to analyze the data. Results: According to the findings, there were no significant difference between the two groups regarding demographic charachteristics. At the baseline, the mean of anxiety scores were 47.9±11.5 and 49.2±11.5 in the control and intervetion groups, respectively. The anxiety scores diminished in both groups after the surgery, however, the difference was not statistically significant between the two groups (P=0.18). Conclusion: For effective control of anxiety among family members of patients, both informational support and other supportive techniques such as psychological support and meeting other family needs should be considered.